The equilibrium contract rent and reward money under incomplete information in reverse supply chains: A game theoretical approach and computational study. (December 2016) - Hong, I-Hsuan; Dang, Jr-Fong; Lin, Kuan-Wen
Highlights: Product homogeneity affects the unit profit of the recycled products. We propose a decentralized reverse supply chain model with incomplete information. We derive the equilibrium contract rent for the third-party recycler. We investigate the equilibrium reward money for customers returning recycled products. Abstract: Many electronic end-of-life (EOL) products are becoming obsolete sooner due to advances in technology. Hence, manufacturers hire third-party recyclers as subcontractors to recycle brand-name products. A complicated profile of recycling EOL products adds a significant cost burden to the third-party recyclers, while only the manufacturer has a superior understanding of the profile of recycling EOL products (homogeneity degree of EOL products). This paper describes the decision of the manufacturer and the third-party recycler in reverse supply chains under incomplete information of product homogeneity, which affects the unit profit of recycled products. The supply chain model assumes that customers receive reward money for returning obsolete products, and that the manufacturer as a leader and the third-party recycler as a follower determine the contract rent offered to the third-party recycler and the reward money paid to customers, respectively. Both the manufacturer and third-party recycler want to maximize their profit functions. We propose a game theoretical approach to search for the equilibrium contract rent for the third-party recycler and the equilibrium reward money for customers returning products for recycling. We conclude with a discussion of the impact of the contract rent and reward money on the equilibrium solution.